E-CRM FOR SALES OF FASHION PRODUCTS AT JANNAH SIMPANG FOUR BOUTIQUE - Diana Pertiwi; Yessica Siagian; Abdul Karim Syahputra (Jurnal Teknik Informatika (Jutif), 2022)
Sales is the purchase of an item from one party to another by getting money from that party, whether in the form of electronics, clothing, food and others. One of the businesses engaged in the business of selling clothing which includes clothes, pants, bags, shoes and others that are sold to customers is Jannah Boutique. the need for a media in the form of a system that integrates marketing, ordering and customer service into an online-based application that can manage the relationship between the company and its customers. The method used in this research is the concept of Electronic Customer Relationship Management (E-CRM) because it can be a company solution in company service management and can utilize customer databases and their complaints to be input and improvement of the company and can make it easier for customers to place orders (orders) and serve as as a promotional media for company products that can save the company's costs in promoting products to customers. This study resulted in E-CRM on fashion product sales at Jannah boutiques able to integrate existing functions within the company, namely marketing, product sales, information and can improve customer service. The conclusion obtained by E-CRM can improve store performance in service, sales and getting new customers.